2012
DOI: 10.1038/bjc.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of E7080, a multitargeted tyrosine kinase inhibitor, in patients with advanced solid tumours

Abstract: Background:The objectives of this phase I study were to assess the safety and tolerability of E7080 in patients with advanced, refractory solid tumours; to determine the maximum tolerated dose (MTD) and pharmacokinetics profile of E7080; and to explore preliminary evidence of its anti-tumour efficacy.Methods:E7080 was administered orally in escalating doses on a once-daily continuous schedule in 28-day cycles to eligible patients. Samples for pharmacokinetic analyses were collected on days 1, 8, 15 and 22 of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 36 publications
6
140
2
3
Order By: Relevance
“…[20][21][22][23]) that has recently been approved for the treatment of radioiodine-refractory DTC (RR-DTC) on the basis of the results of the SELECT phase III trial (24). Preclinical and phase I evidence of antitumor efficacy in a variety of solid tumor types, including thyroid cancer (25)(26)(27)(28), prompted the initiation of a phase II trial in advanced, unresectable progressive MTC and RR-DTC, stratified by histology (29). Here, we present results from the MTC component of the study.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23]) that has recently been approved for the treatment of radioiodine-refractory DTC (RR-DTC) on the basis of the results of the SELECT phase III trial (24). Preclinical and phase I evidence of antitumor efficacy in a variety of solid tumor types, including thyroid cancer (25)(26)(27)(28), prompted the initiation of a phase II trial in advanced, unresectable progressive MTC and RR-DTC, stratified by histology (29). Here, we present results from the MTC component of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib has shown promising antitumor efficacy in advanced solid tumors (16,17,19,20). Preliminary studies suggested the use of up to 25 mg once daily lenvatinib for solid tumors in phase I studies (19,20) and 24 mg once daily was used as the starting dose in patients with solid tumors in subsequent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from inhibiting angiogenesis by targeting endothelial cells [4][5][6][7], lenvatinib exerts a direct effect on tumor cells, by inhibiting their migration and invasion [8]. Promising antitumor effects of lenvatinib were observed in Phase I trials [9,10], leading to a number of disease-specific phase 2 and phase 3 trials with lenvatinib as a single agent or in combination with other anticancer agents.…”
Section: Introductionmentioning
confidence: 99%